Multi-objective optimization on thermo-structural performance of honeycomb absorbers for concentrated solar power systems - Masoud Behzad; Sébastien Poncet; Cristóbal Sarmiento-Laurel (Case Studies in Thermal Engineering)
Honeycomb volumetric solar receivers have emerged as promising candidates for concentrating solar power applications because of their thermal and mechanical properties, enabling the efficient heating of fluids. Despite their potential, challenges remain in optimizing channel design and operating conditions to enhance thermodynamic performance. This study identifies design and operating configurations that maximize the thermodynamic performance and structural reliability of silicon carbide honeycomb volumetric solar receivers, focusing on thermal efficiency and factor of safety. We adopted a multi-objective optimization approach by integrating computational fluid dynamics, heat transfer, and thermal stress analysis. To streamline computational efforts, the Taguchi method was employed, reducing the number of required simulations while maintaining a relative error below 5 %. A critical mass flow to absorbed power ratio of 5 × 10−6 (kg/s)/W was identified, beyond which thermal efficiency stabilizes, providing practical guidance for operational optimization. The optimal configuration achieved a thermal efficiency of 89.3 % and a factor of safety of 87.3 %, with a channel width of 3 mm, a thickness of 0.3 mm, an outlet static pressure of −70 Pa, and a radiation flux of 650 kW/m2. These findings establish a robust framework for optimizing honeycomb receivers, addressing thermal and structural performance while maintaining simplicity in manufacturing processes.